ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI DIVIDEND PAYOUT RATIO (Studi Kasus Pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2011-2013) - Aristanto, Bryan; Prasetiono, Prasetiono (Faculty of Economics and Business Diponegoro University, 2015)
This research was conducted to examine the effect of variable Insider Ownership, Debt to Equity Ratio, Return on Assets, and Firm Size on Dividend Policy.The sampling technique using purposive sampling method on manufacturing companies listed in Indonesia Stock Exchange (BEI) in 2011-2013. From 152 listed companies, acquired 15 companies that meet the specified criteria on the research period from 2011 to 2013. The analysis technique used in this study is multiple regression which includes classical assumption test consisting of normality test, multicollinearity multicollinearity test, autocorrelation test and test heteroscedasticity. While hypothesis tested by F test and t test.The results showed that the variables Insider Ownership and Debt to Equity Ratio have negative effect on Dividend Policy but not significantly. While the Return On Asset and Firm Size have positive significant effect on the Dividend Payout Ratio. Based on the analysis of statistical test F significance value of 0.000 (less than 0.05), so it can be concluded that the variable Insider Ownership, Debt to Equity Ratio, Return on Assets, and Firm Size jointly have a significant effect on Dividend Policy, Predictive ability of the four variables of the Dividend Policy is 54.9%, as indicated by the adjusted R-square of 54.9% while the remaining 45.1% influenced by other factorsnot included in the model study.